Pengaruh Faktor Mindset dan Motivasi Terhadap Minat Berwirausaha Mahasiswa Universitas HKBP Nommensen Medan - Hombing, Katarina Uli P. Br.; Sihombing, Natalia E.; Degodona, L. Primawati (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2025)
Entrepreneurial interest among students is a key factor in fostering young, innovative, and independent entrepreneurs. This study aims to analyze the influence of mindset and motivation on the entrepreneurial interest of students at HKBP Nommensen University, Medan. Mindset, particularly a growth mindset, plays a crucial role in shaping adaptive thinking and openness to business opportunities, while motivation, both intrinsic and extrinsic, serves as a primary driver in making entrepreneurial decisions. This research employs a quantitative method with a survey approach. Data were collected through questionnaires distributed to students from various study programs who have an interest in entrepreneurship. Multiple linear regression analysis was used to examine the relationship and influence of independent variables (mindset and motivation) on the dependent variable (entrepreneurial interest). The results indicate that a positive entrepreneurial mindset significantly enhances students' interest in starting a business. Additionally, motivation, especially internal factors such as the drive for financial independence and self-actualization, strongly influences students' decisions to pursue entrepreneurship. Therefore, universities need to develop a more practical entrepreneurship curriculum and implement programs that foster entrepreneurial mindset and motivation to encourage more students to become entrepreneurs.